From trash to treasure: tumor draining lymph nodes as a multi-omics goldmine in cancer therapy - Li, Yina; Chen, Zihan; Guo, Zhikun; Yu, Jiangnan; Lu, Jianan; Wang, Lei; Zhou, Qian (Frontiers in Oncology, 2025)
Tumor draining lymph nodes (TDLNs), as secondary lymphoid organs, are pivotal in initiating and regulating adaptive immune responses. Historically, TDLNs were recognized primarily as metastasis gateways in cancer, promoting radical dissection to prevent recurrence. However, emerging preclinical studies reveals their critical role in orchestrating systemic anti-tumor immune responses during cancer therapy, highlighting the dilemma of balancing lymph nodes (LNs) preservation with metastasis control. This review traces the evolving understanding of TDLN biology in oncology, from the era of radical LN dissection to multi-omics-driven insights, and synthesizes their dual roles as immune hubs and metastatic niches across first-line clinical therapies (e.g., immunotherapy, radiotherapy, chemotherapy, targeted therapy, etc.). We further propose the concept of “Lymph Node Multi-modal Protective Research (LNMPR)”, emphasizing the prospective value of integrating multi-omics technologies, including spatial transcriptomics, single-cell profiling, and imaging, to decode LN immune dynamics and optimize therapeutic responses. By bridging mechanistic insights with clinical strategies, LN-centric immune modulation may open up a new path for precise tumor treatment.